Male Breast Lesions: A review of 124 cases diagnosed by Fine Needle Aspiration Cytology - Al-Atrooshi, SAZAN A.; Talal, LUBAB F.; AL-Alwan, NADA A. (Journal of the Faculty of Medicine Baghdad, 2008)
Background:Gynecomastia and breast cancer are the two most common diseases of the male breast. Most other diseases found in male breast arise from the skin and subcutaneous tissues. Male breast cancer is relatively rare, in contrast to gynecomastia, which is relatively common. Objectives: The aim of this report is to determine the prevalence of the different breast lesions among males; based upon the findings of fine needle aspiration cytology . Patients and method:This study was carried out within the Main Referral Training Center for Early Detection of Breast Tumors, Medical City Teaching Hospital, Baghdad (from the beginning of January 2003 till the end of November 2007). One hundred twenty four males presenting with different breast lesions were included; all were subjected to physical breast examination, ultrasonography of the breast and fine-needle aspiration. Results:Pathologically, 112 cases (90.3%) were diagnosed as benign lesions, including: 103 cases (83.1%) of gynecomastia, and 9 cases (7.2%) of other miscellaneous benign lesions: six cases (4.8%) diagnosed as inflammatoty conditions [three cases of acute mastitis and three cases of suberolar abscess], two cases (1.6%) diagnosed as granlomatous mastitis, and one case (0.8%) as lipoma. On cytological examination, 14 cases (13.6%) of gynecomastia showed varying degree of cellular atypia. Breast cancer was diagnosed in twelve patients (9.7%); all were infilterative ductal carcinoma. The mean age of patients with gynecomastia was 20.3 years, while it was 61.8 years in breast cancer patients. Sixty six cases (53.2%) of male breast masses were located within the left breast, 47 cases (37.9%) were located within the right breast, while eleven cases (8.9%0) were bilateral (all were gynecomastia). The chief complaints of patients with gynecomastia were as follows: painless mass in 38 cases (30.7%), painful mass in 45 cases (36.3%), pain without mass in 13 cases (10.5), while evidence of bilateral swelling was observed in seven cases (5.6%). Ten patients (8.1%) with breast cancer presented with painless mass, while in only two (1.6%) the chief complaint was painful lump. On ultrasonographic examination of patients with gynecomastia, 58 conditions (46.7%) presented with proliferation of fibroglandular tissue (no definite mass), 35 conditions (28.2%) showed well defined discoid lesions, while in ten cases (8.1%) the findings revealed ill defined retroareolar masses. On the other hand, in patients diagnosed as having male breast carcinoma, the ultrasound findings showed ill defined eccentric masses in eight cases (6.5%) and multiple masses in four (3.2%). Most cases of gynecomastia were idiopathic since patients gave no history of hormonal therapy or exposure to other relevant risk factors. Conclusions:Most palpable masses in the male breast are due to gynecomastia followed by breast carcinoma. Because both present clinically as palpable masses, fine-needle aspiration cytology is extremely useful for the diagnosis.